Planning Assignments of the Italian Metropolitan Cities. Early Trends - Mazzeo, Giuseppe (TeMA - Journal of Land Use, Mobility and Environment, 2017)
The last stage of the process of establishment of the Italian Metropolitan Cities, which took place in 2014, follows of a few decades the start of this institutional reform. In 1990, in fact, the Act 142 (Local Autonomies Reform) had planned metropolitan areas as the administrative organization more suitable to provide these territories of structures for the management and the strategic development alike the best international models. The paper proposes to analyse the first activities taken by the Italian Metropolitan Cities in the sector of territorial government, three years after the enactment in 2014 of Act nr. 56. Focal point of the analysis is the jurisdiction in the formation of two plans (the Strategic Plan and the Metropolitan Territorial Plan) and the following relationships among them, in the logical assumption that between them a necessary and strict consistency there should be. In the first part, the paper analyses some factors characterizing the metropolitan areas and the functions that the law assigns to the new institution in the territorial government sector. The second part outlines the updated situation with regard to the formation of the sectoral tools (Strategic Plan, Territorial Plan and homogeneous zones). The third part analyses the progresses in three Metropolitan Cities taken as sample (Milan, Genoa and Bologna) and, in general, to those of Southern Italy. In the last part, the paper exposes some considerations regarding the issues raised in the article, particularly about the innovativeness of the tools and the timeline for the implementation of the act.